ANALISIS PENERAPAN MODEL PURCHASING POWER PARITY UNTUK MEMPREDIKSI NILAI TUKAR RUPIAH TERHADAP US DOLLAR (Periode Januari 2016 – Desember 2018) - Maqbulla Arochman; Matheous Tamonsang (Jurnal GeoEkonomi, 2020)
ABSTRACT This study aims to test the ability of the purchasing power parity model used to predict the exchange rate of the rupiah against the US dollar based on differences in inflation in the two countries. Determination of the sample in this study using purposive sampling method by time series per month during the period January 2016 - December 2018 as many as 36 months. The results of this study are that first, the difference in inflation rates in Indonesia and the United States has a significant effect on changes in the US Dollar exchange rate. Second, the purchasing power parity model is still feasible to be used to predict the rupiah exchange rate against the US dollar. These results are shown by the significant effect of differences in inflation in the two countries on changes in exchange rates, supported by the regression results of purchasing power parity that meet the requirements of the assumption test. Keywords: Purchasing Power Parity, Rupiah, Dollar, Inflation